Дослідження хімічного складу донних відкладів р. Чаплинка - Богиня, О. С.; Омеліч, І. Ю.; Пікареня, Д. С.; Bohynia, O. S.; Omelich, I. Y.; Pikarenia, D. S. (Дніпровський державний технічний університет, 2019)
The article deals with the material composition of bottom sediments and their dumps, formed after the clearing of channels, on the example of the Chaplinka river. To assess their material composition, studies were conducted to determine the content of organic matter in bottom silt and the chemical composition of ash samples. The results indicate that the material dumps can be a source of secondary pollution of the river and surrounding soils, so it can not be left on the shore.
Investigation of chemical composition of the Chaplinka river bottom sediments
Keywords: bottom sediments; small rivers; mud; pollution of the river